PERANGKAT LUNAK MOBILE USAHA KECIL DAN MENENGAH (UKM) KOTA PALEMBANG - Mirza, Ahmad Haidar; Putra, Ade (JURNAL ILMIAH MATRIK, 2017)
Abstract: This study was conducted to design a mobile software that is expected to help Usaha Kecil dan Menengah (UKM) in Palembang City in marketing their product. This is related to the problems often faced by UKM that is difficult to do marketing products and costs are very high to make a promotion of products. With this mobile software can facilitate and help the UKM in Palembang City to introduce their products to the wider community. In this research of UKM mobile software design is using two (2) methods which is Database Lifecycle Method for database design that will be used and Rapid Application Model (RAD) method for designing User Interface. Keywords: Mobile, UKM, Database Lifecycle dan Rapid Application Development (RAD)